A roadmap of career capital accrual for knowledge workers - Froneman, Sarel (2013)
Knowledge workers need to understand, leverage and capitalise on the new world of work to progress their careers through accumulating career competencies. Career capital is the concept of cumulative career competencies that are of value to the field of the individual’s work. A need exists for greater understanding of career path opportunities available and a possible sequence of accrual. This research adopts an exploratory approach and aims to probe rather than answer questions arising out of the need for more understanding. A qualitative methodology was used through a series of semi-structured but in-depth interviews on a sample of knowledge workers of engineers and information technology workers. The roadmap of career capital accrual for knowledge workers (Figure 5) transpired from empirical research findings founded from within the literature. The model concludes that career capital is accumulated along a recognisable path and sequence and that career gates generally act as reflection opportunities for workers. Not all workers enter these career gates, but value creation and career capital formation is possible for both workers entering and staying behind to specialise and optimise. The outcome of this research could support knowledge workers in unlocking value from their careers, making them more sufficient in creating careers with knowledge that is sought after by organisations. The research outcome could also facilitate organisations to retain top talent by understanding their career capital accrual approach. Copyright === Dissertation (MBA)--University of Pretoria, 2010. === Gordon Institute of Business Science (GIBS) === unrestricted